Nicotine-mediated effects in neuronal and mouse models of synucleinopathy - Fares, Mohamed Bilal; Alijevic, Omar; Johne, Stephanie; Overk, Cassia; Hashimoto, Makoto; Kondylis, Athanasios; Adame, Anthony; Dulize, Remi; Peric, Dariusz; Nury, Catherine; Battey, James; Guedj, Emmanuel; et al. (Frontiers in Neuroscience, 2023)
Alpha-synuclein (α-Syn) aggregation, transmission, and contribution to neurotoxicity represent central mechanisms underlying Parkinson’s disease. The plant alkaloid “nicotine” was reported to attenuate α-Syn aggregation in different models, but its precise mode of action remains unclear. In this study, we investigated the effect of 2-week chronic nicotine treatment on α-Syn aggregation, neuroinflammation, neurodegeneration, and motor deficits in D-line α-Syn transgenic mice. We also established a novel humanized neuronal model of α-Syn aggregation and toxicity based on treatment of dopaminergic neurons derived from human induced pluripotent stem cells (iPSC) with α-Syn preformed fibrils (PFF) and applied this model to investigate the effects of nicotine and other compounds and their modes of action. Overall, our results showed that nicotine attenuated α-Syn-provoked neuropathology in both models. Moreover, when investigating the role of nicotinic acetylcholine receptor (nAChR) signaling in nicotine’s neuroprotective effects in iPSC-derived dopaminergic neurons, we observed that while α4-specific antagonists reduced the nicotine-induced calcium response, α4 agonists (e.g., AZD1446 and anatabine) mediated similar neuroprotective responses against α-Syn PFF-provoked neurodegeneration. Our results show that nicotine attenuates α-Syn-provoked neuropathology in vivo and in a humanized neuronal model of synucleinopathy and that activation of α4β2 nicotinic receptors might mediate these neuroprotective effects.